The Contribution of Green Social Workers in Addressing the Impacts of Climate Change in Indonesia - Jaka Ramdani; Budhi Gunawan; Rudi Saprudin Darwis (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2022)
Climate change is part of natural disasters accompanied by the process of environmental degradation and harms human life holistically. The impact of climate change has become a serious problem experienced by various society levels, without any exception. Numerous scientific studies explain that climate change triggers various environmental changes that threaten the survival and welfare of society. Climate change adaptation and mitigation become the preventive and repressive strategies for controlling climate change. A continously developed programis the Climate Village Program (Proklim). The main basis of the program is community empowerment to be able to run sustainably. The present research focused on the study of roles, referring to the theory of Green Social Work by Lena Dominelli. The data were analyzed descriptively regarding the role of Green Social Workers concerning the suitability between the theory and practice. The application of the qualitative approach employed in this research was in the form of a case study. The researchers decided to employ the case study method because the what was investigated in this study was considered unique regarding the role of Green Social Workers in the Climate Village Program, which has been developed and implemented by the government. The roles of Green Social Workers were, first, helping to analyze and solve problems and respond to opportunities and challenges faced by farmers in managing their businesses; second, facilitating the learning process of farmers or Forest Farmer Group (KTH) in implementing good and sustainable business governance; third, assisting farmers, Forest Farmer Group (KTH), or community groups in developing institutions to be competitive and productive; fourth, improving the leadership, managerial, and entrepreneurial skills of farmers, Forest Farmer Group (KTH), or community groups;fifth, ensuring farmers' access to information, technology, and other resources in business development, and assisting as well as supervising farmers in improving production and productivity; sixth, being a safeguard of state assets in the form of forests, inviting the community to know, want, and participate in maintaining and protecting forest resources from various forest; seventh, encouraging the community to sustainably adapt and mitigate climate change; eighth, initiating the establishment of the Climate Village Program. Green Social Workers were indispensable in community empowerment, especially in encouraging environmental improvement to remain sustainable for the community's prosperity.